Eksplicitna in implicitna uporaba vzorcev pri razvoju informacijskih rešitev - Heričko, Marjan (Uporabna informatika (Ljubljana), 2003)
The application of components and frameworks with corresponding design patterns is basic for contemporary software development. This article demonstrates the usage of fundamental design patterns in modern programming languages and points out the difference between implicit and explicit usage of design patterns. Implicit usage means that the developer is not aware of the whole structure of the design pattern, but he can nevertheless successfully exploit its benefits. Explicit usage requires in-depth understanding of the design pattern. Our research has shown that the internal structure of used patterns is not simple. The fact is that design patterns can be combined into compound patterns in a similar way as other software components. Our findings have shown that it is possible to use all three basic types of abstractions with design patterns: classification, aggregation and generalization. The article shows that awareness and understanding of appropriate design patterns are crucial for successful development and application of software components, especially server-side components. The role and manner of the design pattern usage define the required level and depth of understanding of it.
Keywords: design patterns; informacijske rešitve; information solutions; načrtovalski vzorci; patterns; programming languages; programski jeziki; razvoj programske opreme; software development; vzorci